(untitled) (Fiep Bulletin - online, 2014)
This article is part of the context of the body as culturally inserted in Brazilian society. Where the design of the body bound in contemporary society focuses excessively on the valuation body, which establishes the body as object and mechanized operation, designed as a capital. This way of conceiving it is very closely tied to a standard body culturally imbricated in which such default gets accepted as correct and ideal for a large part of the population, endorsing a body image ideal. This conceive it, the appreciation of the subject is characterized as acceptable only glimpsed by the outside, the interior of each shall be missed. In an attempt to overcome this capitalist form and mechanistic design the body appealed to the later work of Michel Foucault to seek, in this author, particularly on the issue of self-care, parameters to consider to what extent this feature enables to go beyond the limits of mechanization body. For this we will try to link the concept of self care, by its dimensions and characteristics, the body, and also explore the relationship of this concept with the theme of aesthetics of existence. And in this context, seeking a training process significant to the subjects through self care globally in all aspects and dimensions of the human being, for only thus can prove to be a real self-care.